Architecture Information Design of Internal Quality Assurance Agency Stt Ibnu Sina Batam Using Enterprise Architecture Planning (EAP) - Ropianto, M; ., Larisang; Dhaini Rova, John (International Journal of Engineering and Technology, 2018)
STT Ibnu Sina Batam is a private university that strives to improve the quality both in terms of quality of academic and administrative services. Therefore STT Ibnu Sina should continued to improve the quality of assurance system related to the collecting, processing and presentation of academic evaluation data so it can produce a clear picture of the needs at various levels of stakeholders in order to maintain the quality of the academic process in STT Ibnu Sina Batam. Internal quality control activities also one form of monitoring and evaluation to measure the achievement of the vision and mission of STT Ibn Sina predetermined. In designing the information architecture to help the performance of the Internal Quality Insurance Agency (LPMI) STT Ibnu Sina Batam, authors choose Enterprise Architecture Planning (EAP) as method. To represent a blueprint of collecting, processing and presentation of evaluation result data and information of the quality assurance STT Ibnu Sina Batam.Â